ANNIVERSARY OF THE 1967 OUTER SPACE TREATY - O. A. Volynskaya (Московский журнал международного права, 2018)
Introduction. On 10 October 2017 the Treaty on Principles Governing the Activities of States in the Exploration and Use of Outer Space, including the Moon and Other Celestial Bodies (Outer Space Treaty) celebrated fifty years from the day of its entry into force. In this same year, the world celebrates another memorable event – 60 years of the space era, which began with the successful launch of the first artificial Earth satellite. These dates once again reminded the global community that technological progress is inseparable from international law, as well as of the importance of the rule of law in such a unique sphere of human activity as outer space.Materials and methods. The materials for the article were the works of Russian and foreign researchers in the field of international space law as well as the main international treaties governing the activities of states in the exploration and use of outer space, Resolutions of the UN General Assembly, reports of the Legal Subcommittee of the UN Committee on the Peaceful Uses of Outer Space. As for the methodology, the author opted to employ popular scientific research methods (including dialectics, analysis and synthesis, deduction and induction, comparative legal and historical analysis).Research results. Over the past decades, the international space law (ISL) has changed, but the Outer Space Treaty, which established the basic principles of the exploration and use of outer space, remains a reliable foundation for the global space activities. With the development of private space activities specific separate states attempt to govern aspects of such activities at the national level bypassing the imperative requirements of the Outer Space Treaty. In this respect a problem of due and authentic interpretation of universal norms of the ISL is of particular relevance, which would correspond to the interests of all participants of space activities.Discussion and conclusions. In recent years the Legal Subcommittee of the UN Committee on the Peaceful Uses of Outer Space (UN COPUOS) has heard statements that the provisions of the Outer Space Treaty are “obsolete” and “do not correspond to reality”. It seems possible to disagree with this characteristic. For half a century none of the basic principles established in the Treaty have been challenged, both States members to the Treaty (as of 10 October 2017, 106 states ratified the Treaty and another 24 signed it) and other countries that still have not joined it respect these basics and adhere to them. The Outer Space Treaty has fulfilled its aim: to preserve outer space peaceful, weapons-free and accessible for exploration and use by all states on the basis of equality and non-discrimination.